Gas population effects in harmonic emission by plasmonic fields - (:unkn) unknown (AMER PHYSICAL SOC, 2013)
We theoretically investigate the boosts in high-order harmonic generation using fabricated nanostructures and determine that the distribution of an ensemble of gas atoms in the vicinity of nanostructures is substantial for the evaluation of harmonic emission. The distributional behavior is mimicked by a single-atom response as well as by allowing the target atoms to reside in different positions inside the nanogap. For a given population distribution, a maximum photon energy of similar to 25 eV could be observed in qualitative agreement with experiment.
Keywords: GENERATION; ENHANCEMENT